Real-world cabazitaxel safety: the Italian early-access program in metastatic castration-resistant prostate cancer. (May 2014) - Bracarda, Sergio; Gernone, Angela; Gasparro, Donatello; Marchetti, Paolo; Ronzoni, Monica; Bortolus, Roberto; Fratino, Lucia; Basso, Umberto; Mazzanti, Roberto; Messina, Caterina; Tucci, Marcello; Boccardo, Francesco; et al.
ABSTRACT: Aim: Cabazitaxel is a novel taxane that is approved for use in metastatic castration-resistant prostate cancer based on the Phase III TROPIC study, which showed improved overall survival with cabazitaxel/prednisone versus mitoxantrone/prednisone. A global early-access program was initiated in order to provide early access to cabazitaxel in docetaxel-pretreated patients and to obtain real-world data.Patients & methods: We report interim safety results from an Italian prospective, single-arm, multicenter, open-label trial of 218 patients receiving cabazitaxel 25 mg/m2 every 3 weeks plus prednisolone 10 mg/day, until disease progression, unacceptable toxicity, investigator's decision or death.Results: Patients completing treatment received a median of six cabazitaxel cycles. The most common grade 3/4 adverse events were neutropenia (33.9%), leukopenia (15.6%), anemia (6%) and asthenia (6%). No peripheral neuropathy or nail disorders were observed.Conclusion: These results confirm that cabazitaxel has a manageable safety profile in daily clinical practice and support its use in patients with prostate cancer who progress during or after a docetaxel-based therapy.